The Influence of Brand Image, Product Innovation and Social Media Marketing on Samsung Smartphone‘s Buying Interest: Case Study on Narotama University Students - Prama Wildan Ardiansyah; Sengguruh Nilowardono (LPPM of NAROTAMA UNIVERSITY)
The purpose of this study is to examine the influence of Brand Image, Product Innovation and Social Media Marketing on Samsung Smartphone Buying Interest. The independent variables of this study are brand image, product innovation and social media marketing, while the dependent variable is buying interest. This is a quantitative research. The sample counted 100 respondents the data is collected through surveys from questioner tool. The data were analyzed using multiple linear regression and using the SPSS version 16.00. The results showed that Brand Image (X1), Product Innovation (X2) and Social Media Marketing (X3) have a positive and significant influence simultaneously on Samsung smartphone buying interest (Y). Brand Image variable (X1) does not have a significant influence partially on buying interest (Y). The adjusted R square value is 0.609 which means that the influence of independent variables on the dependent variable is 60.9%.